Anti-Osteoporotic Activity of an Edible Traditional Chinese Medicine Cistanche deserticola on Bone Metabolism of Ovariectomized Rats Through RANKL/RANK/TRAF6-Mediated Signaling Pathways - Zhang, Bo; Yang, Ling-Ling; Ding, Shu-Qin; Liu, Jing-Jing; Dong, Yan-Hong; Li, Yan-Ting; Li, Nan; Zhao, Xiao-Jun; Hu, Chang-Ling; Jiang, Yiping; Ma, Xue-Qin (Frontiers in Pharmacology, 2019)
In view of the limitations of existing therapeutic methods for treatment of postmenopausal osteoporosis, there still remains a need for more options with both efficacy and less adverse effects. Cistanches deserticola Y. C. Ma is known as a commonly used tonic herb in Asian counties and was traditionally used to treatment deficiency of kidney energy including muscle weakness in minority area. Based on the theory of “kidney dominate bone”, an ovariectomized (OVX) rat model of postmenopausal osteoporosis was used to evaluate the therapeutic effect of C. deserticola extract (CDE) on bone lost. 48 female Sprague-Dawley rats, aged about 12 weeks, were randomly assigned into 6 groups including sham group orally administrated with 0.5% CMC-Na (SHAM), positive group treated with 1 mg/kg of estradiol valerate (EV), low, moderate and high dosage groups treated with 200, 400 and 800 mg/kg of CDE, respectively. After 3 months of continuous intervention, CDE exhibited significant anti-osteoporotic activity evidenced by the enhanced total bone mineral density, ameliorated bone microarchitecture, increased alkaline phosphatase activity, decreased deoxypyridinoline, cathepsin K, tartrate-resistant acid phosphatase and malondialdehyde levels; whereas the increased body weights as well as decreased uterus and vagina weights in OVX rats were not influenced by CDE intervention. In addition, a seemed contradictory phenomenon on contents of calcium and phosphorus between OVX and SHAM rats were observed and elucidated. Mechanistically, CDE significantly down-regulated the levels of TRAF6, RANKL, RANK, NF-κB, IKKβ, NFAT2 and up-regulated the PI3K, AKT, osteoprotegerin and c-Fos expressions, which implied CDE could suppress RANKL/RANK-induced activation of downstream NF-κB and PI3K/AKT pathways, and ultimately, preventing activity of the key osteoclastogenic proteins NFAT2 and c-Fos. All of the data suggested CDE possessed potential anti-osteoporotic activity and this effect was, at least in part, involved in modulation of RANKL/RANK/TRAF6-mediated NF-κB and PI3K/AKT signaling as well as c-Fos and NFAT2 levels. Therefore, CDE may represent a useful promising remedy candidate for treatment of postmenopausal osteoporosis.